Pengujian Validitas dan Reliabilitas Instrumen Resilience Siswa SMK Teknik Ketenagalistrikan menggunakan PLS-SEM - Siti Shofiyatus Sa’diyah; Tri Wrahatnolo; Joko Joko; Yulia Fransisca (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
In education, resilience is an important psychological concept especially for understanding how students cope with stress and challenges in their educational environment. This study focuses on five dimensions that contribute to students' level of resilience, including: perseverence, self-reliance, equanimity, existential aloness, and meaningfull life. Study aims to test the validity and reliability of a scale or instrument that measures the level of resilience in Vocational High School (SMK) students, using Structural Equation Modeling Partial Least Squares (SEM-PLS). This study involved 103 SMK students as research participants. Data were collected through a previously developed resilience scale. Data were analyzed using measurement model and structural model. The analysis showed that the resilience scale has good construct validity, with reliable indicators to measure the desired construct. The reliability of the instrument was also found to be high based on the calculated Cronbach's alpha coefficient. This study makes an important contribution to understanding the resilience of vocational students and validating an instrument that can be used to effectively measure this concept in an educational context. Practical implications of the findings include the development of more targeted educational programs to enhance students' resilience, so that they can face learning and life challenges more readily and effectively.